Antecedents of Muslims’ Intention to Buy Halal Korean Food: Study In Indonesia - Nadia Firza Faradina; Istyakara Muslichah (Universitas Airlangga, 2022)
ABSTRAK Penelitian ini bertujuan untuk menginvestigasi faktor-faktor yang memengaruhi Muslim di Indonesia berniat untuk membeli makanan Korea bersertifikasi Halal MUI. Metode sampling yang digunakan yaitu teknik purposive sampling dengan kriteria Muslim di Indonesia yang mengetahui makanan Korea bersertifikasi Halal MUI dan berusia > 18 tahun. Penelitian ini mendapatkan 190 responden dan data diolah menggunakan metode PLS-SEM. Variabel yang digunakan dalam penelitian ini yaitu pengetahuan tentang makanan Halal, sikap, religiusitas, dan niat beli. Hasil dari penelitian ini menunjukkan bahwa pengetahuan tentang makanan Halal dan religiusitas memengaruhi sikap terhadap makanan Korea bersertifikasi Halal MUI secara positif dan signifikan. Pengetahuan tentang makanan Halal dan sikap juga memengaruhi niat beli makanan Korea bersertifikasi Halal MUI secara positif dan signifikan. Namun, religiusitas ditemukan tidak memengaruhi niat beli makanan Korea bersertifikasi Halal MUI. Hasil penelitian ini diharapkan dapat membantu pelaku bisnis pada industri makanan Korea untuk mengembangkan aspek apa saja yang dapat meningkatkan niat beli Muslim terhadap makanan Korea bersertifikasi Halal MUI. Kata Kunci: pengetahuan, sikap, religiusitas, niat beli, makanan Korea, makanan halal. ABSTRACT This study aims to investigate factors that influence Indonesian Muslims to purchase Korean food with MUI Halal certification. This study uses a purposive sampling technique with criteria: Muslims in Indonesia who know Korean food with MUI Halal certification and aged > 18 years. This study obtained 190 respondents and the data was processed using PLS-SEM method. The variables used in this study are knowledge of Halal food, attitudes, religiosity, and purchase intentions. The results of this study indicate that knowledge about Halal food and religiosity affects attitudes towards Korean food with MUI Halal certification positively and significantly. Knowledge about Halal food and attitudes also positively and significantly influence the intention to buy Korean food with MUI Halal certification. However, religiosity was found to not affect the intention to buy Korean food with MUI Halal certification. The results of this study are expected to help businesses in Korean food industry to develop aspects that can increase Muslim’s purchase intentions for MUI Halal certified Korean food. Keywords: knowledge, attitude, religiosity, purchase intention, Korean food, halal food. DAFTAR PUSTAKA Abd Rahman, A., Asrarhaghighi, E., & Ab Rahman, S. (2015). Consumers and halal cosmetic products: Knowledge, religiosity, attitude and intention. Journal of Islamic Marketing, 6(1), 148–163. https://doi.org/10.1108/JIMA-09-2013-0068 Aji, H. M. (2017a). Does skepticism toward halal label exist ? The empirical evidence from Indonesia 8th Global Islamic Marketing Conference Proceedings, 184-195. Aji, H. M. (2017b). Examining the moderating role of high-versus-low scepticism toward halal labels: findings from Indonesia. International Journal of Islamic Marketing and Branding, 2(4), 278. https://doi.org/10.1504/ijimb.2017.10010054 Arli, D. and Tjiptono, F. (2014). The end of religion? Examining the role of religiousness, materialism, and long-term orientation on consumer ethics in Indonesia. Journal of Business Ethics, 123(3), 385-400. Astuti, Y., & Asih, D. (2021). Country of origin, religiosity and halal awareness: A case study of purchase intention of Korean food. Journal of Asian Finance, Economics and Business, 8(4), 0413–0421. https://doi.org/10.13106/jafeb.2021.vol8.no4.0413 Aziz, S., Md Husin, M., Hussin, N., & Afaq, Z. (2019). Factors that influence individuals’ intentions to purchase family takaful mediating role of perceived trust. Asia Pacific Journal of Marketing and Logistics, 31(1), 81–104. https://doi.org/10.1108/APJML-12-2017-0311 Bashir, A. M. (2019). Effect of halal awareness, halal logo and attitude on foreign consumers’ purchase intention. British Food Journal, 121(9), 1998–2015. https://doi.org/10.1108/BFJ-01-2019-0011 Bohari, A. M., Hin, C. W., & Fuad, N. (2013). An analysis on the competitiveness of halal food industry in Malaysia: An approach of SWOT and ICT strategy. Malaysia Journal of Society and Space, 9(1), 1–11. Cooper, D. R., & Schindler, P. S. (2014). Business research methods. New York: Mcgraw-hill. Fathy, A., Younus, S., Rasheed, F., & Zia, A. (2015). Identifying the factors affecting customer purchase intention. Global Journal of Management and Business Research: Administration and Management, 15(2), 1–6. Fornell, C., Larcker, D. F. (1981). Evaluating structural equation models with unobservable variables and measurement error. Journal of Marketing Research, 18(1), 39-50. https://doi.org/10.1177%2F002224378101800104 Graafland, J. (2017). Religiosity, attitude, and the demand for socially responsible products. Journal of Business Ethics, 144(1), 121–138. https://doi.org/10.1007/s10551-015-2796-9 Hair, J., Hult, G. T., Ringle, C., & Sarstedt, M. (2017). A primer on partial least squares structural equation modeling (PLS-SEM). New York: Sage Publishing. Hennida, C. (2013). Corporate strategies in the spread of hallyu (Korean Wave) in Indonesia. Mozaik, 13(2), 117–125. https://doi.org/10.20473/mozaik.v13i2.3833 Jeong, J. S., Lee, S. H., & Lee, S. G. (2017). When Indonesians routinely consume Korean pop culture: Revisiting Jakartan fans of the Korean drama Dae Jang Geum. International Journal of Communication, 11, 2288–2307. Khan, A., Arafat, M. Y., & Azam, M. K. (2020). Role of halal literacy and religiosity in buying intention of halal branded food products in India. Journal of Islamic Marketing, 13(2), 287-308. https://doi.org/10.1108/JIMA-08-2019-0175 Memon, Y. J., Azhar, S. M., Haque, R., & Bhutto, N. A. (2020). Religiosity as a moderator between theory of planned behavior and halal purchase intention. Journal of Islamic Marketing, 11(6), 1821–1836. https://doi.org/10.1108/JIMA-01-2019-0006 Nadhifah, N., Eka, S., & Tusita, A. (2019). Halal Korean food and glocalization. https://doi.org/10.4108/eai.23-3-2019.2284943 Rizkitysha, T. L., & Hananto, A. (2020). Do knowledge, perceived usefulness of halal label and religiosity affect attitude and intention to buy halal-labeled detergent? Journal of Islamic Marketing, 13(3), 649-670. https://doi.org/10.1108/JIMA-03-2020-0070 Singhapakdi, A., Vitell, S. J., Lee, D. J., Nisius, A. M., & Yu, G. B. (2013). The influence of love of money and religiosity on ethical decision-making in marketing. Journal of Business Ethics, 114(1), 183–191. https://doi.org/10.1007/s10551-012-1334-2. Usman, H., Chairy, C., & Projo, N. W. K. (2021). Impact of Muslim decision-making style and religiosity on intention to purchasing certified halal food. Journal of Islamic Marketing, Vol. ahead-of-print No. ahead-of-print. https://doi.org/10.1108/JIMA-01-2021-0027 Wang, Y., Wiegerinck, V., Krikke, H., & Zhang, H. (2013). Understanding the purchase intention towards remanufactured product in closed-loop supply chains: An empirical study in China. International Journal of Physical Distribution and Logistics Management, 43(10), 866–888. https://doi.org/10.1108/IJPDLM-01-2013-0011